Comparison of CD4+ T Cells in HIV-infected patients with Tuberculosis and non HIV infected patients with tuberculosis After anti tuberculous treatemnt. - Zaman, Khushal Khan; Misra, Samrendra; Rakue, Yasuyuki; Shah, Syed Nasir; Bowtuanuwong, Churerrat; Khan, Raza Muhammad (Journal of Postgraduate Medical Institute, 2011)
A prospective study of CD4+ T lymphocytes along the course of treatment among 25 HIV infected patients with active tuberculosis (TB) receiving antituberculous drugs was compared with 32 non HIV infected patients with active TB also receiving the same regime. Teh CD4+ T cell count among non HIV infected patients was 525 + 415/mm which increased to 675 + 378/mm and 902 + 267/mm at the third and sixth month of therapy respectively. Among HIV-infected patietns, the CD4+ T cell count was 72 + 45/mm which decreased to 50 + 25/mm and 42 + 20/mm at the third and sixth months of therapy (P< 0.05).